2018
DOI: 10.1111/pbr.12609
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and gene action controlling yield and yield components in bread wheat (Triticum aestivum L.) under drought‐stressed and nonstressed conditions

Abstract: This study determined the combining ability and gene action controlling yield and yield‐related traits in wheat under drought‐stressed and nonstressed conditions. Twelve parents possessing Rht‐B1b and Rht‐D1a genes and their 66 half‐diallel crosses were evaluated under field and glasshouse conditions. Plant height (PH), productive tiller number (TN), kernels per spike (KPS), thousand seed weight (TSW) and grain yield (GY) were recorded. Analysis of variance, heritability, correlation and combining ability anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
4
16
0
1
Order By: Relevance
“…Similarly, most South African hybrid lines with short stature had a lower yield in greenhouse experiments and in field trials under dry conditions. Here the authors concluded that the ideal stature for wheat should be optimized to an intermediate plant height (Mwadzingeni, Shimelis, & Tsilo, 2018).…”
Section: Grain Yield In Semi-dwarf Wheat Plants Is Often Lower Thanmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, most South African hybrid lines with short stature had a lower yield in greenhouse experiments and in field trials under dry conditions. Here the authors concluded that the ideal stature for wheat should be optimized to an intermediate plant height (Mwadzingeni, Shimelis, & Tsilo, 2018).…”
Section: Grain Yield In Semi-dwarf Wheat Plants Is Often Lower Thanmentioning
confidence: 99%
“…Therefore, the proposed ideotype of wheat stature may be precisely tuned and optimized to a moderately reduced plant height, as suggested earlier (Mwadzingeni et al, 2018;Richards, 1992a) but with improved drought tolerance.…”
Section: Some Semi-dwarf Mutant Alleles Offer a Promising Alternatimentioning
confidence: 99%
“…The differences between those results and our study may be due to differences in the level of salt stress, different genetic backgrounds, and/or screening environment used. Concerning thousand seed weight and grain yield, Mwadzingeni et al (2018) observed significant effects for GCA under normal and drought-stress conditions indicated the influence of additive gene action.…”
Section: Discussionmentioning
confidence: 95%
“…Some genotypes showed great heat tolerance and gave the highest grain yield per plant under both sowing dates was observed Khajuria et al (2016) and Ali et al (2020). Heritability estimates were moderate for grain yield (Sharma et al (2010), Ahmad et al, 2017 andMwadzingeni et al, 2018). High heritability in broad sense estimates for days to heading (Singh et al, 2013 andElbasier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%